Air electrode / separator assembly and metal-air secondary battery
Patent Information
- Application Number
- CN202280047492.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2021-08-26
- Filing Date
- 2022-06-23
- Publication Date
- 2026-10-16
- Estimated Expiration
- 2042-06-23
AI Technical Summary
该由锌枝晶引起的短路导致反复充放电寿命缩短
Smart Images

Figure CN117751474B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to an air electrode / separator junction and a metal-air secondary battery. Background Technology
[0002] Metal-air batteries are a candidate for innovative batteries. In metal-air batteries, oxygen, the active material of the positive electrode, is supplied from the air. Therefore, the space within the battery container can be maximized for filling the negative electrode active material, thus theoretically enabling higher energy density. For example, in zinc-air batteries using zinc as the negative electrode active material, an alkaline aqueous solution such as potassium hydroxide is used as the electrolyte, and a separator (wall) is used to prevent short circuits between the positive and negative electrodes. During discharge, as shown in the following reaction equation, O2 is reduced to OH- on the air electrode (positive electrode) side. - On the other hand, at the negative electrode, zinc is oxidized to form ZnO.
[0003] Positive electrode: O2 + 2H2O + 4e - →4OH -
[0004] Negative electrode: 2Zn + 4OH - →2ZnO+2H2O+4e -
[0005] However, it is known that in zinc-air batteries, nickel-zinc batteries, and other zinc-based secondary batteries, during charging, metallic zinc precipitates from the negative electrode in a dendritic form, penetrating the gaps in the non-woven fabric separator and reaching the positive electrode, resulting in a short circuit. This short circuit caused by zinc dendrites shortens the battery life under repeated charge-discharge cycles. Furthermore, zinc-air batteries also suffer from the problem that carbon dioxide from the air passes through the air electrode and dissolves in the electrolyte, precipitating basic carbonates and degrading battery performance. The same problems can also occur in lithium-air batteries.
[0006] To address the aforementioned problems, batteries incorporating layered double hydroxide (LDH) separators have been proposed, which allow hydroxide ions to selectively permeate while preventing zinc dendrites from penetrating. For example, Patent Document 1 (International Publication No. 2013 / 073292) discloses that in a zinc-air secondary battery, an LDH separator is placed between the air electrode and the negative electrode to prevent short circuits between the positive and negative electrodes caused by zinc dendrites and to prevent the ingress of carbon dioxide. Furthermore, Patent Document 2 (International Publication No. 2016 / 076047) discloses a separator structure incorporating an LDH separator fitted or bonded to a resin frame, and discloses that the LDH separator possesses high density, exhibiting a degree of air and / or water impermeability. This document also discloses that the LDH separator can be composited with a porous substrate. Furthermore, Patent Document 3 (International Publication No. 2016 / 067884) discloses various methods for forming a dense LDH film on the surface of a porous substrate to obtain a composite material (LDH separator). This method includes the steps of uniformly attaching a starting material capable of providing a crystallization starting point for LDH to the porous substrate, and performing hydrothermal treatment on the porous substrate in an aqueous solution of the raw material to form a dense LDH film on the surface of the porous substrate.
[0007] Furthermore, in the field of metal-air secondary batteries such as zinc-air secondary batteries, air electrode / separator joints with an air electrode layer disposed on an LDH separator have been proposed. Patent Document 4 (International Publication No. 2015 / 146671) discloses an air electrode / separator joint in which an air electrode layer comprising an air electrode catalyst, an electron-conducting material, and a hydroxide ion-conducting material is provided on the LDH separator. Patent Document 5 (International Publication No. 2020 / 246176) discloses an air electrode / separator joint comprising: an LDH separator or other hydroxide ion-conducting dense separator; an interface layer comprising a hydroxide ion-conducting material and a conductive material; and an air electrode layer comprising an outermost catalyst layer composed of layered double hydroxide (LDH) covering a porous current collector and its surface. The hydroxide ion-conducting material contained in this interface layer has the morphology of multiple plate-like particles, which are bonded to the main surface of the hydroxide ion-conducting dense separator in a vertical or inclined manner. In this patent document 5, the LDH separator is disclosed in the form of a separator containing LDH and / or LDH-like compounds, which are defined as hydroxides and / or oxides that have a layered crystalline structure similar to LDH, although they may not be called LDH.
[0008] Existing technical documents
[0009] Patent documents
[0010] Patent Document 1: International Publication No. 2013 / 073292
[0011] Patent Document 2: International Publication No. 2016 / 076047
[0012] Patent Document 3: International Publication No. 2016 / 067884
[0013] Patent Document 4: International Publication No. 2015 / 146671
[0014] Patent Document 5: International Publication No. 2020 / 246176 Summary of the Invention
[0015] However, the air electrode reaction in a metal-air battery occurs at a three-phase interface (composed of a hydroxide ion-conducting phase, an electron-conducting phase, and a gas phase) where hydroxide ions, oxygen, and electrons are all present. Therefore, it is desirable to ensure as much of the reaction field as possible within the air electrode. In this regard, in metal-air batteries that typically employ porous polymer separators, the electrolyte can easily penetrate into the air electrode due to the porous nature of the separator. Therefore, the electrolyte can handle hydroxide ion conduction within the air electrode, and high ion conductivity can be expected. However, as a strong base, the electrolyte has a low dissolved oxygen content. Therefore, if the catalyst is covered by the electrolyte, the oxygen supply to the catalyst is insufficient. As a result, it is believed that the reaction mostly occurs on the catalyst present at the interface between the electrolyte and the gas phase; that is, the reaction field is confined to the interface between the electrolyte and the gas phase. In addition, the metal-air battery using a porous polymer separator described above is an open system. Therefore, there are the following problems: potassium carbonate is generated in the air electrode due to carbon dioxide in the air, which blocks the pores; or the resistance of the electrolyte gradually increases due to carbon dioxide permeating through the separator.
[0016] On the other hand, in metal-air batteries using hydroxide ion-conducting separators such as LDH separators, the airtightness of the separators prevents electrolyte from intruding into the air electrode. Therefore, the aforementioned problems caused by carbon dioxide can be avoided. However, a solid-phase hydroxide ion conductor is required to allow the reaction to occur within the air electrode. In this case, hydroxide ion conduction can maximize the reaction field. However, compared to air batteries that use electrolytes as the hydroxide ion conduction medium (air batteries using porous polymer separators), the solid resistivity of the hydroxide ion conductor is higher than that of the electrolyte. Furthermore, the interfacial resistance between solids cannot be ignored. Therefore, the conduction or diffusion of hydroxide ions may become a bottleneck (rate control stage) relative to the conduction or diffusion of electrons and gases.
[0017] However, as mentioned above, metal-air secondary batteries using hydroxide ion-conducting dense separators such as LDH separators have the excellent advantage of preventing short circuits between the positive and negative electrodes caused by metal dendrites and preventing carbon dioxide contamination. Furthermore, they also have the advantage of suppressing the evaporation of moisture in the electrolyte due to the density of the hydroxide ion-conducting dense separator. Therefore, it is desirable to fully utilize these advantages while reducing the problems associated with hydroxide ion conduction or diffusion.
[0018] The inventors of this invention have recently come to the following insight: by providing an air electrode layer with a thickness of less than 1000 nm on one side of a hydroxide ion conducting separator, an air electrode / separator junction can be provided to reduce the diffusion resistance caused by the conduction or diffusion of electrons, gases and hydroxide ions, reduce the interfacial resistance between solids, and thereby achieve a reduction in battery resistance.
[0019] Therefore, the object of the present invention is to provide an air electrode / separator joint that reduces diffusion resistance and interfacial resistance between solids due to the conduction or diffusion of electrons, gases and hydroxide ions, thereby enabling a reduction in battery resistance.
[0020] According to the present invention, the following solution is provided.
[0021] [Option 1]
[0022] An air electrode / separator joint, wherein:
[0023] A hydroxide ion-conducting separator containing a hydroxide ion-conducting solid electrolyte;
[0024] An air electrode layer with a thickness of less than 1000 nm is disposed on one side of the hydroxide ion conducting separator and includes a hydroxide ion conducting material, an electron conducting material, and an air electrode catalyst (wherein, the hydroxide ion conducting material can be the same material as the hydroxide ion conducting solid electrolyte or the air electrode catalyst, and the electron conducting material can be the same material as the air electrode catalyst).
[0025] [Option 2]
[0026] According to the air electrode / separator joint described in Scheme 1, wherein...
[0027] The air electrode / separator junction also includes an interface layer between the hydroxide ion-conducting separator and the air electrode layer.
[0028] The interface layer includes:
[0029] Multiple plate-shaped particles are composed of a hydroxide ion-conducting solid electrolyte that grows in a direction away from the surface of the hydroxide ion-conducting separator;
[0030] An electronically conductive material configured to fill the gaps between the plurality of plate-like particles and / or the irregularities formed by the plurality of plate-like particles.
[0031] [Option 3]
[0032] According to the air electrode / separator joint described in Scheme 2, wherein...
[0033] The air electrode layer comprises:
[0034] Multiple electronically conductive units are disposed on the interface layer with gaps between them and are made of the electronically conductive material; and
[0035] The hydroxide ion-conducting material and the air electrode catalyst are disposed on the electron conduction unit.
[0036] [Option 4]
[0037] According to the air electrode / separator joint described in scheme 2 or 3, wherein...
[0038] The thickness of the interface layer is less than 150 nm, and the thickness of the air electrode layer is less than 300 nm.
[0039] [Option 5]
[0040] According to the air electrode / separator joint described in Scheme 1, wherein...
[0041] The air electrode layer comprises a plurality of plate-shaped particles consisting of the hydroxide ion-conducting solid electrolyte growing in a direction away from the surface of the hydroxide ion-conducting separator.
[0042] The plurality of plate-like particles are at least partially covered by the electron-conducting material.
[0043] The air electrode catalyst is supported on the plurality of plate-like particles that are at least partially coated with the electron-conducting material.
[0044] [Option 6]
[0045] According to the air electrode / separator joint described in Scheme 5, wherein...
[0046] The thickness of the air electrode layer is less than 800 nm.
[0047] [Option 7]
[0048] According to any one of Schemes 1 to 6, the air electrode / separator joint wherein...
[0049] The hydroxide ion-conducting material contained in the air electrode layer is a layered double hydroxide (LDH) and / or an LDH-like compound.
[0050] The electron-conducting material contained in the air electrode layer is at least one selected from the group consisting of metallic materials, conductive ceramics, and carbon materials.
[0051] The air electrode catalyst contained in the air electrode layer is selected from at least one of the following groups: layered double hydroxide (LDH) and other metal hydroxides, metal oxides, metal nanoparticles and carbon materials.
[0052] [Option 8]
[0053] According to any one of Schemes 2 to 4, the air electrode / separator joint wherein...
[0054] The hydroxide ion-conducting material contained in the interface layer is a layered double hydroxide (LDH) and / or an LDH-like compound.
[0055] [Option 9]
[0056] According to any one of Schemes 1 to 8, the air electrode / separator joint wherein...
[0057] The hydroxide ion-conducting solid electrolyte is a layered double hydroxide (LDH) and / or an LDH-like compound, thereby the hydroxide ion-conducting separator becomes an LDH separator.
[0058] [Option 10]
[0059] According to the air electrode / separator joint described in Scheme 9, wherein...
[0060] The LDH partition is composited with a porous substrate.
[0061] [Option 11]
[0062] A metal-air secondary battery, wherein...
[0063] It comprises: an air electrode / separator junction as described in any one of claims 1 to 10, a metal negative electrode, and an electrolyte, wherein the electrolyte is separated from the air electrode layer by means of the hydroxide ion-conducting separator. Attached Figure Description
[0064] Figure 1 This is a schematic cross-sectional view and an enlarged view of an air electrode / partition assembly according to one embodiment of the present invention.
[0065] Figure 2 This is a schematic cross-sectional view and an enlarged view of an air electrode / partition assembly according to another embodiment of the present invention.
[0066] Figure 3 This is a schematic cross-sectional view of the hydroxide ion-conducting separator used in the present invention.
[0067] Figure 4A This is a schematic diagram illustrating an example of a He transmittance measurement system.
[0068] Figure 4B yes Figure 4A A simplified cross-sectional view of the sample holder and its surrounding area used in the measurement system shown. Detailed Implementation
[0069] Air electrode / partition joint
[0070] Figure 1 The diagram illustrates one embodiment of the air electrode / separator assembly of the present invention. Figure 1 The air electrode / separator junction 10 shown includes a hydroxide ion-conducting separator 12 and an air electrode layer 14, which is disposed on one side of the hydroxide ion-conducting separator 12. The hydroxide ion-conducting separator 12 contains a hydroxide ion-conducting solid electrolyte. The air electrode layer 14 contains a hydroxide ion-conducting material 16, an electron-conducting material 18, and an air electrode catalyst 20. The hydroxide ion-conducting material 16 can be the same material as the hydroxide ion-conducting solid electrolyte or the air electrode catalyst 20. The electron-conducting material 18 can be the same material as the air electrode catalyst 20. Furthermore, the thickness of the air electrode layer 14 is 1000 nm or less. By providing an air electrode layer 14 with a thickness of 1000 nm or less on one side of the hydroxide ion-conducting separator 12, the diffusion resistance and interfacial resistance between solids caused by the conduction or diffusion of electrons, gases, and hydroxide ions are reduced, thereby reducing the battery resistance.
[0071] That is, as described above, in metal-air batteries using hydroxide ion-conducting separators such as LDH separators, the density of the separators can suppress the intrusion of electrolyte into the air electrode. Therefore, the aforementioned problems caused by carbon dioxide can be avoided. However, in order for the reaction to occur within the air electrode, a solid-phase hydroxide ion conductor is required. In this case, hydroxide ion conduction can expand the reaction field as much as possible. However, compared with air batteries that use electrolytes as hydroxide ion conduction media (air batteries using porous polymer separators), the solid resistance of the hydroxide ion conductor is higher than that of the electrolyte. Furthermore, the interfacial resistance between solids cannot be ignored. Therefore, the conduction or diffusion of hydroxide ions may become a bottleneck (rate control stage) relative to the conduction or diffusion of electrons and gases. In this regard, the air electrode / separator junction 10 effectively eliminates this problem. This is because: by making the thickness of the air electrode layer 14 extremely thin, less than 1000 nm, the air electrode reaction can be completed within the small space of the air electrode layer 14. That is, the movement distances of electrons, gas, and hydroxide ions (especially the diffusion distances of gas and hydroxide ions, which are prone to causing diffusion resistance problems) can be shortened within this tiny space, thereby reducing diffusion resistance and interfacial resistance between solids. This allows for a reduction in battery resistance in batteries with the embedded air electrode / separator junction 10. Furthermore, because the air electrode layer 14 is extremely thin, no material is wasted in its formation; the air electrode layer 14 can be formed with a very small amount of material, thus allowing for the efficient use of even expensive catalysts.
[0072] Based on this, the air electrode / separator junction 10 can be made very thin, thus enabling it to be flexible. In this case, the air electrode / separator junction 10 can be flexed even when pressurized, and therefore can be housed within a battery container and pressurized together with other battery elements (such as negative electrodes) in a direction that seals the battery elements together. This pressurization is particularly advantageous when multiple air electrode / separator junctions 10 are alternately embedded in a battery container along with multiple metal negative electrodes to form a stacked battery. Similarly, it is also advantageous when multiple stacked batteries are housed in a single module container to form a battery module. For example, by pressurizing the zinc-air secondary battery, the gap that allows zinc dendrite growth between the negative electrode and the hydroxide ion-conducting separator 12 is minimized (preferably eliminated), thereby more effectively preventing zinc dendrite extension. For example, the preferred thickness of the air electrode / separator joint 10 is 10 to 200 μm, more preferably 15 to 180 μm, and even more preferably 20 to 130 μm.
[0073] The hydroxide ion-conducting separator 12 is defined as: a separator containing a hydroxide ion-conducting solid electrolyte, specifically utilizing the hydroxide ion conductivity of the solid electrolyte to selectively allow hydroxide ions to pass through. Therefore, the hydroxide ion-conducting separator is impermeable to air and / or water, particularly impermeable to air. That is, the hydroxide ion-conducting material constitutes all or part of the hydroxide ion-conducting dense separator with a high degree of density exhibiting impermeability to air and / or water. The hydroxide ion-conducting dense separator can be composited with a porous substrate.
[0074] Preferably, the hydroxide ion-conducting solid electrolyte is a layered double hydroxide (LDH) and / or an LDH-like compound (hereinafter collectively referred to as hydroxide ion-conducting layered compounds), thereby making the hydroxide ion-conducting separator 12 an LDH separator. That is, an LDH separator is defined as a separator containing LDH and / or LDH-like compounds (hereinafter collectively referred to as hydroxide ion-conducting layered compounds), and specifically utilizing the hydroxide ion conductivity of the hydroxide ion-conducting layered compounds to selectively allow hydroxide ions to pass through. In this specification, "LDH-like compound" refers to hydroxides and / or oxides with a layered crystalline structure that may not be called LDH but is similar to LDH, and can be called equivalents of LDH. However, as a broad definition, "LDH" can also be interpreted as including not only LDH but also LDH-like compounds. This LDH separator can be a separator known as those disclosed in Patent Documents 1-5, and is preferably an LDH separator composited with a porous substrate. Figure 3 As shown in summary, the particularly preferred LDH separator, namely the hydroxide ion-conducting separator 12, comprises a porous substrate 12a made of polymeric material and a hydroxide ion-conducting layered compound 12b that seals the pores P of the porous substrate. This LDH separator will be described below. Because it contains a porous substrate made of polymeric material, it can bend even under pressure and is not easily cracked. Therefore, it can be housed in a battery container and pressurized together with other battery elements (such as negative electrodes) in a direction that tightly seals the battery elements together. This pressurization is particularly advantageous when multiple air electrode / separator joints 10 are alternately embedded in the battery container along with multiple metal negative electrodes to form a stacked battery. Similarly, it is also advantageous when multiple stacked batteries are housed in a single module container to form a battery module. For example, by pressurizing the zinc-air secondary battery, the gap that allows zinc dendrite growth between the negative electrode and the LDH separator is minimized (preferably eliminated), thereby more effectively preventing zinc dendrite extension.
[0075] The air electrode layer 14 comprises a hydroxide ion-conducting material 16, an electron-conducting material 18, and an air electrode catalyst 20. The hydroxide ion-conducting material 16 can be the same material as the hydroxide ion-conducting solid electrolyte or the air electrode catalyst 20. Examples of such materials include LDHs containing transition metals (e.g., Ni-Fe-LDH, Co-Fe-LDH, and Ni-Fe-V-LDH). Alternatively, Mg-Al-LDH can be an example of a hydroxide ion-conducting material that does not also function as an air electrode catalyst. Furthermore, the electron-conducting material 18 can be the same material as the air electrode catalyst 20. Examples of such materials include carbon materials, metal nanoparticles, nitrides such as TiN, and LaSr3Fe3O4. 10 wait.
[0076] The hydroxide ion-conducting material 16 contained in the air electrode layer 14 can be any material with hydroxide ion conductivity, and is not particularly limited, but is preferably LDH and / or LDH-like compounds. The composition of LDH is not particularly limited, but the preferred basic composition is the general formula: M 2+ 1-x M 3+ x (OH)2A n- x / n ·mH2O (where M) 2+ M is at least one or more divalent cations. 3+ A is at least one trivalent cation. n- For anion with an n-valence, where n is an integer greater than or equal to 1, x is between 0.1 and 0.4, and m is any real number. In the above general formula, M 2+ It can be any divalent cation; as a preferred example, Ni can be cited. 2+ Mg 2+ Ca 2+ Mn 2+ Fe 2+ Co 2 + Cu 2+ Zn 2+ M 3+ It can be any trivalent cation; as a preferred example, Fe can be cited. 3+ V 3+ Al 3+ Co 3+ Cr 3+ In 3 + In particular, to ensure that LDH possesses both catalytic performance and hydroxide ion conductivity, M is preferred. 2+ and M 3+ These are transition metal ions, respectively. From this perspective, a more preferred M...2+ For Ni 2+ Mn 2+ Fe 2+ Co 2+ Cu 2+ Isovalent transition metal ions, especially Ni 2+ On the other hand, a more preferred M 3+ For Fe 3+ V 3+ Co 3+ Cr 3+ Trivalent transition metal ions, especially Fe 3+ V 3+ and / or Co 3+ In this case, M 2+ A portion can be made from Mg 2+ Ca 2+ Zn 2+ Replacement with metal ions other than transition metals, and M 3+ A portion can be made by Al 3+ In 3+ Replacement with metal ions other than transition metals. A n- It can be any anion; as a preferred example, NO can be cited. 3- CO3 2- SO4 2- OH - Cl - I - ,Br - F - NO is preferred. 3- and / or CO3 2- Therefore, the preferred general formula is: M 2+ Contains Ni 2+ M 3+ Contains Fe 3+ A n- Contains NO 3- and / or CO3 2- n is an integer greater than or equal to 1, preferably 1 to 3. x is between 0.1 and 0.4, preferably 0.2 to 0.35. m is any real number. More specifically, m is greater than or equal to 0, typically a real number or integer greater than or equal to 1.
[0077] The electron-conducting material 18 contained in the air electrode layer 14 is preferably at least one selected from the group consisting of metallic materials, conductive ceramics, and carbon materials. In particular, examples of conductive ceramics include LaNiO3 and LaSr3Fe3O4. 10Examples of carbon materials include: carbon black, graphite, carbon nanotubes, graphene, reduced graphene oxide, and any combination thereof, but are not limited to these; various other carbon materials can also be used. Examples of metallic materials include: nickel, titanium, stainless steel, etc.
[0078] The air electrode catalyst 20 contained in the air electrode layer 14 is preferably at least one selected from the group consisting of LDH and other metal hydroxides, metal oxides, metal nanoparticles, and carbon materials, and more preferably at least one selected from the group consisting of LDH, metal oxides, metal nanoparticles, and carbon materials. For LDH, as described above regarding hydroxide ion-conducting materials, it is particularly ideal to possess both the functions of an air electrode catalyst and a hydroxide ion-conducting material. Examples of metal hydroxides include Ni-Fe-OH, Ni-Co-OH, and any combination thereof, which may further contain a third metal element. Examples of metal oxides include Co3O4, LaNiO3, and LaSr3Fe3O4. 10 And any combination thereof. Examples of metal nanoparticles (typically metal particles with a particle size of 2–30 nm) include Pt, Ni-Fe alloys, etc. Examples of carbon materials, as mentioned above, include carbon black, graphite, carbon nanotubes, graphene, reduced graphene oxide, and any combination thereof, but are not limited to these; various other carbon materials can also be used. From the viewpoint of improving the catalytic performance of carbon materials, carbon materials preferably also contain metal elements and / or other elements such as nitrogen, boron, phosphorus, and sulfur.
[0079] The thickness of the air electrode layer 14 is less than 1000 nm, preferably 30 to 800 nm, more preferably 50 to 600 nm, and even more preferably 80 to 500 nm.
[0080] Hereinafter, preferred embodiments of the air electrode / partition joint of the first embodiment of the present invention will be described, and the first and second embodiments will be described.
[0081] (First Implementation)
[0082] like Figure 1As shown, the air electrode / separator joint 10 of the first embodiment also provides an interface layer 13 between the hydroxide ion conducting separator 12 and the air electrode layer 14. The interface layer 13 includes: a plurality of plate-shaped particles 12p, which are composed of a hydroxide ion conducting solid electrolyte grown in a direction away from the surface of the hydroxide ion conducting separator 12 (a direction perpendicular or inclined relative to the surface); and an electron conducting material 18, which is configured to fill the gaps between the plurality of plate-shaped particles 12p and / or the irregularities formed by the plurality of plate-shaped particles 12p. In this embodiment, by filling the gaps and irregularities caused by the plate-shaped particles 12p grown in a direction away from the hydroxide ion conducting separator 12 with the electron conducting material 18, the interface layer 13 can be used as an interface layer that undertakes electron conduction in the in-plane direction of the hydroxide ion conducting separator 12 and hydroxide ion conduction in a direction perpendicular to the main surface of the hydroxide ion conducting separator 12 (the thickness direction of the hydroxide ion conducting separator 12 and the air electrode layer 14). In particular, the plate-like particles 12p of hydroxide ion-conducting solid electrolytes such as LDH and / or LDH-like compounds have the characteristic of hydroxide ion conduction along the plate surface direction (in the case of LDH, the (003) plane direction). Therefore, it is believed that by arranging the plate-like particles 12p in a direction away from the surface of the LDH separator 12, the interfacial resistance between the air electrode layer 14 and the LDH separator 12 is reduced. In particular, if the microstructure of the surface of the LDH separator 12 manufactured according to known methods is observed, then... Figure 1 As shown, typically, LDH plate-like particles 12p grow in a direction away from the surface of LDH separator 12. In this invention, the presence of plate-like particles 12p (hydroxide ion-conducting material 16) and electron-conducting material 18 between LDH separator 12 and air electrode layer 14 in this state can significantly reduce the interface resistance.
[0083] The air electrode layer 14 in the first embodiment preferably includes: a plurality of electron conduction units 18a, which are disposed on the interface layer 13 with gaps between them and are made of electron conduction material 18; and a hydroxide ion conduction material 16 and an air electrode catalyst 20, which are disposed on the electron conduction units 18a. Accordingly, air can enter the air electrode layer 14 efficiently, thereby increasing the area of the reaction field (the three-phase interface formed by the hydroxide ion conduction phase, the electron conduction phase and the gas phase).
[0084] The thickness of the interface layer 13 in the first embodiment is preferably 150 nm or less, more preferably 30 to 150 nm, and even more preferably 50 to 130 nm. Furthermore, the thickness of the air electrode layer 14 in the first embodiment is preferably 300 nm or less, more preferably 20 to 250 nm, even more preferably 40 to 200 nm, and even more preferably 50 to 180 nm.
[0085] The hydroxide ion-conducting material 16 contained in the interface layer 13 in the first embodiment is preferably LDH and / or LDH-like compounds. When the hydroxide ion-conducting separator 12 is an LDH separator, plate-like particles of LDH and / or LDH-like compounds are present on the surface of a typical LDH separator, and therefore, these particles can be used as plate-like particles 12p.
[0086] The air electrode / partition joint 10 of the first embodiment can be manufactured in, for example, the following order.
[0087] 1) Electron conductive material 18 is deposited on the surface of hydroxide ion conductive separator 12 by filling the gaps and unevenness caused by the plate-shaped particles 12p of the hydroxide ion conductive solid electrolyte grown from the LDH separator or other hydroxide ion conductive separator 12. The electron conductive material 18 used here can be a mixture of a material with high water repellency and a material with high electron conductivity.
[0088] 2) The electron-conducting material 18 is deposited in such a way that multiple electron-conducting units 18a that are separated from each other are formed, thus ensuring gaps, in the gaps and uneven surfaces of the hydroxide ion-conducting separator 12 obtained in 1) above, which are filled with the electron-conducting material 18.
[0089] 3) The air electrode catalyst 20 is deposited on the electron conduction unit 18a obtained in 2) above. At this time, the air electrode catalyst 20 can function as both the hydroxide ion conduction material 16 and the electron conduction material 18.
[0090] 4) A precursor of hydroxide ion-conducting material 16 (e.g., LDH) is deposited on the electron-conducting unit 18a in which the air electrode catalyst 20 is deposited in 3) above. Examples of such precursors include metallic materials such as Ni-Fe alloys.
[0091] 5) The material obtained in step 4) above is subjected to alkali treatment to convert the precursor into a hydroxide ion-conducting material 16 (e.g., LDH). This yields the air electrode / separator joint 10 of the first embodiment.
[0092] Regarding the deposition method (or film formation method) of each material in 1) to 4) above, there is no particular limitation as long as an air electrode layer 14 with the desired thickness and function can be formed. Considering the ease of controlling the thickness and the ease of handling various compositions, the deposition method (or film formation method) using the gas phase is advantageous. As preferred examples of the deposition method using the gas phase, sputtering and laser ablation can be mentioned, and bipolar sputtering and magnetron sputtering are particularly preferred. In the case of using laser ablation, the hydroxide ion conducting material 16 (e.g., LDH) itself can be used to replace the precursor of the hydroxide ion conducting material 16 (e.g., LDH) in 4) above. In this case, 5) above can be omitted.
[0093] (Second Implementation)
[0094] Figure 2 The image shows an air electrode / separator assembly 10' according to a second embodiment. In the air electrode / separator assembly 10', the air electrode layer 14 includes a plurality of plate-like particles 12p, which are composed of a hydroxide ion-conducting solid electrolyte (equivalent to hydroxide ion-conducting material 16) grown in a direction away from the surface of the hydroxide ion-conducting separator 12 (perpendicular or inclined relative to the surface). These plurality of plate-like particles 12p are at least partially covered by an electron-conducting material 18. Furthermore, an air electrode catalyst 20 is supported on the plurality of plate-like particles 12p at least partially covered by the electron-conducting material 18. In this embodiment, the plate-like particles 12p grown in a direction away from the hydroxide ion-conducting separator 12 can be used as the hydroxide ion-conducting material 16. In the case where the hydroxide ion-conducting separator 12 is an LDH separator, plate-like particles of LDH and / or LDH-like compounds are present on the surface of a typical LDH separator, and therefore, these particles can be used as plate-like particles 12p.
[0095] In the second embodiment, the thickness of the air electrode layer 14 is preferably 800 nm or less, more preferably 100-800 nm, even more preferably 150-700 nm, even more preferably 200-600 nm, and even more preferably 300-500 nm.
[0096] The air electrode / partition joint 10' of the second embodiment can be manufactured, for example, in the following order.
[0097] 1) The electron-conducting material 18 is deposited along the uneven surfaces caused by the plate-like particles 12p of the hydroxide ion-conducting solid electrolyte grown from the hydroxide ion-conducting separator 12, such as the LDH separator. Preferably, the electron-conducting material 18 does not completely cover the plate-like particles 12p, but rather partially or completely covers them with gaps that allow for the permeation of, for example, water vapor and oxygen. This ensures efficient and effective control of the reaction field (the three-phase interface formed by the hydroxide ion-conducting phase, the electron-conducting phase, and the gas phase).
[0098] 2) The air electrode catalyst 20 is deposited on the surface of the hydroxide ion-conducting separator 12, on which the electron-conducting material 18 is deposited, obtained in 1) above. This yields the air electrode / separator joint 10' of the second embodiment.
[0099] It should be noted that, as a pretreatment prior to 1) above, the hydroxide ion-conducting solid electrolyte (e.g., LDH) present on the surface of the LDH separator 12, such as the LDH separator, can be roughened. For example, roughening can be performed by briefly immersing the LDH separator in dilute acid for rinsing (i.e., by eroding the LDH present on the surface of the LDH separator with acid). Alternatively, roughening can also be performed by depositing LDH precursors on the surface of the LDH separator and then subjecting it to heating, alkaline treatment, etc., to form coarse LDH particles.
[0100] The deposition method (or film formation method) for each material in 1) and 2) above can be the same as that in the first embodiment. For example, as step 1) above, nickel (or carbon) can be deposited on the surface of the LDH separator where plate-like particles of Mg-Ti-Al-LDH are grown in a direction away from the surface by sputtering using a nickel target (or carbon target). In addition, as step 2) above, cobalt targets, manganese targets, and carbon targets can be used to deposit carbon nanoparticles doped with manganese and cobalt as air electrode catalyst 20.
[0101] Metal-air secondary battery
[0102] As described above, the air electrode / separator junction 10 is preferably used in a metal-air secondary battery. That is, according to a preferred embodiment of the invention, a metal-air secondary battery is provided, comprising: an air electrode / separator junction 10, a metal negative electrode, and an electrolyte, the electrolyte being separated from the air electrode layer 14 by means of an LDH separator 12. A zinc-air secondary battery using a zinc electrode as the metal negative electrode is particularly preferred. Alternatively, a lithium-air secondary battery using a lithium electrode as the metal negative electrode may also be used.
[0103] Preferred LDH partition
[0104] The preferred embodiment of the LDH partition 12 of the present invention will be described below. As described above, the LDH partition 12 of this embodiment is as follows: Figure 3 Structurally shown, it includes: a porous substrate 12a, and a hydroxide ion-conducting layered compound 12b, which is an LDH and / or LDH-like compound. It should be noted that... Figure 3 The region of the hydroxide ion-conducting layered compound 12b is depicted as not connected between the upper and lower surfaces of the LDH separator 12 because it is depicted in two dimensions in cross-sectional form. However, considering the depth in three dimensions, the region of the hydroxide ion-conducting layered compound 12b is connected between the upper and lower surfaces of the LDH separator 12, thereby ensuring the hydroxide ion conductivity of the LDH separator 12. The porous substrate 12a is made of a polymer material, and the hydroxide ion-conducting layered compound 12b seals the pores of the porous substrate 12a. However, the pores of the porous substrate 12a do not need to be completely sealed; slight residual pores P may remain. By highly densifying the pores of the polymer porous substrate 12a by sealing them with the hydroxide ion-conducting layered compound 12b, an LDH separator 12 that can more effectively suppress short circuits caused by zinc dendrites can be provided.
[0105] Furthermore, the LDH separator 12 of this solution possesses the desired ionic conductivity required for a separator due to the hydroxide ion-conducting layered compound 12b, and also exhibits excellent flexibility and strength. This is because the polymer porous substrate 12a contained in the LDH separator 12 itself possesses both flexibility and strength. That is, with the pores of the polymer porous substrate 12a fully sealed by the hydroxide ion-conducting layered compound 12b, the LDH separator 12 becomes dense. Therefore, it is a seamlessly integrated material that is highly composite of the polymer porous substrate 12a and the hydroxide ion-conducting layered compound 12b. Thus, it can be said that the rigidity and brittleness caused by the hydroxide ion-conducting layered compound 12b, which is a ceramic material, are offset or mitigated by the flexibility and strength of the polymer porous substrate 12a.
[0106] The LDH separator 12 of this design is expected to have very few residual pores P (pores not sealed by the hydroxide ion-conducting layered compound 12b). Because of the residual pores P, the LDH separator 12 has an average porosity of, for example, 0.03% or more and less than 1.0%, preferably 0.05% or more and less than 0.95%, more preferably 0.05% or more and less than 0.9%, further preferably 0.05% to 0.8%, and most preferably 0.05% to 0.5%. If the average porosity is within the above range, the pores of the porous substrate 12a are sufficiently sealed by the hydroxide ion-conducting layered compound 12b, resulting in extremely high compactness. Therefore, short circuits caused by zinc dendrites can be suppressed more effectively. Furthermore, a significantly higher ion conductivity can be achieved, and the LDH separator 12 can fully function as a hydroxide ion-conducting compact separator. The average porosity can be determined as follows: a) The LDH septum is polished using a cross-section polisher (CP); b) Cross-sectional images of the functional layer are obtained in two fields of view at a magnification of 50,000 using FE-SEM (field emission scanning electron microscope); c) Based on the image data of the obtained cross-sectional images, the porosity of each of the two fields of view is calculated using image inspection software (e.g., HDevelop, MVTec Software), and the average porosity is obtained.
[0107] The LDH separator 12 is a separator containing a hydroxide ion-conducting layered compound 12b. When embedded in a zinc secondary battery, it separates the positive and negative plates in a manner that enables hydroxide ion conduction. That is, the LDH separator 12 functions as a dense separator for hydroxide ion conduction. Therefore, the LDH separator 12 is airtight and / or watertight. Accordingly, the LDH separator 12 is preferably densified to a degree that makes it airtight and / or watertight. It should be noted that "airtight" in this specification means, as described in Patent Documents 2 and 3, that even when helium gas is brought into contact with one side of the test object in water at a differential pressure of 0.5 atm, no bubbles generated by helium gas are observed from the other side. Furthermore, "watertight" in this specification means, as described in Patent Documents 2 and 3, that water in contact with one side of the test object does not permeate to the other side. That is, the LDH separator 12's impermeability to air and / or water means that it has a high degree of density, preventing the passage of gas or water, and is not a porous membrane or other porous material that is permeable to water or air. Therefore, the LDH separator 12, due to its hydroxide ion conductivity, allows only hydroxide ions to selectively pass through, thus functioning as a battery separator. This makes it a highly effective configuration for preventing short circuits between the positive and negative electrodes caused by the physical prevention of separator penetration due to zinc dendrites generated during charging. Because the LDH separator 12 has hydroxide ion conductivity, the required hydroxide ions can move efficiently between the positive and negative electrodes, thereby enabling the charging and discharging reactions in both electrodes.
[0108] The He permeability per unit area of the LDH separator 12 is preferably 3.0 cm / min·atm or less, more preferably 2.0 cm / min·atm or less, and even more preferably 1.0 cm / min·atm or less. A separator with a He permeability of 3.0 cm / min·atm or less can effectively suppress Zn permeation (typically zinc ions or zincate ions) in the electrolyte. In principle, the separator of this design significantly suppresses Zn permeation, thereby effectively suppressing the growth of zinc dendrites when used in zinc secondary batteries. The He permeability is determined by the following steps: supplying He gas to one side of the separator to allow the He gas to pass through the separator, and calculating the He permeability to evaluate the compactness of the hydroxide ion transport-induced dense separator. The He permeability is calculated using the He gas permeation rate F per unit time, the differential pressure P applied to the separator during He gas permeation, and the membrane area S through which the He gas passes, according to the formula F / (P×S). By evaluating gas permeability using He gas in this way, it is possible to assess whether an extremely high level of compactness exists. Consequently, it is possible to effectively evaluate a high level of compactness that minimizes the permeability of substances other than hydroxide ions (especially Zn, which causes zinc dendrite growth) (allowing only trace amounts to permeate). This is because He gas has the smallest constituent unit among the diverse range of atoms or molecules that can constitute a gas, and its reactivity is extremely low. That is, He does not form molecules but constitutes He gas as He atom monomers. In this respect, hydrogen gas is composed of H2 molecules; therefore, as a gaseous constituent unit, He atom monomers are even smaller. Furthermore, H2 gas is a flammable gas, making it dangerous. Moreover, by employing an index such as He gas permeability defined by the above formula, an objective evaluation of compactness can be easily performed regardless of variations in sample size and measurement conditions. This allows for a simple, safe, and effective evaluation of whether a separator possesses sufficiently high compactness suitable for zinc secondary batteries.
[0109] The He transmittance can be determined preferably in the following order. First, establish... Figure 4A and Figure 4B The He transmittance measurement system 310 is shown. The He transmittance measurement system 310 is configured such that He gas from a gas cylinder filled with He gas is supplied to the sample holder 316 via a pressure gauge 312 and a flow meter 314 (digital flow meter), and is discharged from one side of the LDH partition 318 held on the sample holder 316 to the other side.
[0110] The sample holder 316 has a structure including a gas supply port 316a, a sealed space 316b, and a gas outlet 316c, and is assembled as follows. First, adhesive 322 is applied along the outer periphery of the LDH partition 318, and it is mounted on a clamp 324 (made of ABS resin) with a central opening. Butyl rubber seals are provided at the upper and lower ends of the clamp 324 as sealing members 326a and 326b. Then, support members 328a and 328b (made of PTFE) with openings formed by flanges are used to clamp the sample holder from the outside of the sealing members 326a and 326b. In this way, the sealed space 316b is divided by the LDH partition 318, the clamp 324, the sealing member 326a, and the support member 328a. The support members 328a and 328b are fastened to each other by using a screw fastening mechanism 330, so that He gas will not leak from any part other than the gas outlet 316c. The gas supply port 316a of the sample holder 316 assembled in this way is connected to the gas supply pipe 334 via the connector 332.
[0111] Next, He gas is supplied to the He permeability measurement system 310 via gas supply pipe 334, allowing it to pass through the LDH partition 318 held in the sample holder 316. During this time, the gas supply pressure and flow rate are monitored by pressure gauge 312 and flow meter 314. After He gas permeation for 1–30 minutes, the He permeability is calculated. The He permeability is calculated using the He gas permeation rate F (cm³) per unit time. 3 ( / min), the differential pressure P (atm) applied to the LDH separator during He gas permeation, and the membrane area S (cm²) during He gas permeation. 2 The permeation rate of He gas, F (cm³), is calculated using the formula F / (P×S). 3 The flow rate ( / min) is read directly from flow meter 314. Additionally, the differential pressure P is measured using gauge pressure from pressure gauge 312. It should be noted that He gas is supplied with a differential pressure P ranging from 0.05 to 0.90 atm.
[0112] In the LDH separator 12, a hydroxide ion-conducting layered compound 12b, acting as LDH and / or LDH-like compounds, seals the pores of the porous substrate 12a. It is generally known that LDH consists of multiple hydroxide base layers and intermediate layers between these base layers. The hydroxide base layers are primarily composed of metal elements (typically metal ions) and OH groups. The intermediate layers of LDH consist of anions and H₂O. The anions are ions with a valence of 1 or higher, preferably ions with a valence of 1 or 2. Preferably, the anions in the LDH include OH groups. - and / or CO3 2- In addition, LDH has excellent ionic conductivity due to its inherent properties.
[0113] Typically, it is known that LDH is based on the fundamental formula M 2+ 1-x M 3+ x (OH)2A n- x / n ·mH2O (where M) 2+ M is a divalent cation. 3+ A is a trivalent cation. n- The substance represented by an anion with an n-valence (where n is an integer greater than or equal to 1, x is between 0.1 and 0.4, and m is greater than or equal to 0) is an n-valent anion. In the above basic formula, M... 2+ It can be any divalent cation; as a preferred example, Mg can be cited. 2+ Ca 2+ and Zn 2+ More preferably Mg 2+ M 3+ It can be any trivalent cation; as a preferred example, Al can be cited. 3+ or Cr 3+ Al is preferred. 3+ A n- It can be any anion; as a preferred example, OH- - and CO3 2- Therefore, in the above basic formula, M is preferably... 2+ Contains Mg 2+ M 3+ Includes Al 3+ A n- Contains OH - and / or CO3 2- n is an integer greater than or equal to 1, preferably 1 or 2. x is 0.1 to 0.4, preferably 0.2 to 0.35. m is any number representing the number of moles of water, greater than or equal to 0, typically a real number greater than 0 or 1. However, the above basic composition is merely a formula representing the "basic composition" of LDH in a typical way, and the constituent ions can be appropriately substituted. For example, in the above basic composition, M can be replaced by a cation with a valence of 4 or higher. 3+ Partial or complete substitution can be performed, in which case the anion A in the above general formula can also be appropriately changed. n- The coefficient x / n.
[0114] For example, the hydroxide base layer of an LDH can contain Ni, Al, Ti, and OH groups. The intermediate layer, as described above, consists of anions and H₂O. The alternating stacked structure of the hydroxide base layer and intermediate layer is essentially the same as the commonly known alternating stacked structure of LDH. However, the LDH of this scheme has its hydroxide base layer composed of specified elements or ions including Ni, Al, Ti, and OH groups, thus exhibiting excellent alkali resistance. The reason for this may not be certain, but for the LDH of this scheme, it is believed that the reason is that Al, which was previously thought to be easily soluble in alkaline solutions, is difficult to dissolve in alkaline solutions due to a certain interaction with Ni and Ti. Even so, the LDH of this scheme can still exhibit high ionic conductivity suitable for use as a separator in alkaline secondary batteries. The Ni in the LDH can be in the form of nickel ions. Regarding nickel ions in LDH, Ni is typically considered to be... 2+ However, it can also have Ni 3+ Other valences are not specifically limited. Al in LDH can take the form of aluminum ions. Regarding aluminum ions in LDH, Al is considered to be typical. 3+ However, it can also have other valences, therefore, there are no particular limitations. Ti in LDH can take the form of titanium ions. Regarding titanium ions in LDH, Ti is considered to be typical. 4+ However, it can also have Ti 3+ Other valences are not specifically limited. The hydroxide base layer can contain Ni, Al, Ti, and OH groups, or it can contain other elements or ions. However, it is preferable that the hydroxide base layer contains Ni, Al, Ti, and OH groups as the main components. That is, it is preferable that the hydroxide base layer mainly contains Ni, Al, Ti, and OH groups. Therefore, a typical design for the hydroxide base layer is: composed of Ni, Al, Ti, OH groups and unavoidable impurities depending on the circumstances. Unavoidable impurities are any elements that may inevitably be mixed in during the manufacturing process, for example, they may originate from raw materials or substrates and be mixed into LDH. As mentioned above, the valences of Ni, Al, and Ti are not necessarily determined, therefore, it is impractical or impossible to strictly define LDH with a general formula. Assuming that the hydroxide base layer is mainly composed of Ni 2+ Al 3+ Ti 4+ In the case of OH groups, the basic composition of the corresponding LDH can be represented by the general formula: Ni 2 + 1-x-y Al 3+ x Ti 4+ y (OH)2A n- (x+2y) / n ·mH2O (where A) n-The anion is an n-valent anion, where n is an integer greater than or equal to 1, preferably 1 or 2, 0 < x < 1, preferably 0.01 ≤ x ≤ 0.5, 0 < y < 1, preferably 0.01 ≤ y ≤ 0.5, 0 < x + y < 1, and m is greater than or equal to 0, typically a real number greater than 0 or greater than 1. However, the above general formula should be understood as only the "basic composition," and should be understood as: Ni 2+ Al 3+ Ti 4+ Elements can be replaced by other elements or ions (including elements or ions of the same element with other valences, and elements or ions that may inevitably be mixed in during the preparation process) to a degree that does not impair the basic properties of LDH.
[0115] LDH-like compounds are hydroxides and / or oxides with a layered crystalline structure that, while perhaps not strictly LDH, resembles LDH. Preferred LDH-like compounds will be described below. By using hydroxides and / or oxides with a defined composition—i.e., LDH-like compounds—as the hydroxide ion-conducting material instead of conventional LDH, a hydroxide ion-conducting barrier with excellent alkali resistance and the ability to more effectively suppress short circuits caused by zinc dendrites can be provided.
[0116] As described above, the LDH separator 12 comprises a hydroxide ion-conducting layered compound 12b and a porous substrate 12a (typically composed of a porous substrate 12a and the hydroxide ion-conducting layered compound 12b). In the LDH separator 12, the hydroxide ion-conducting layered compound seals the pores of the porous substrate, thereby giving it hydroxide ion conductivity and air impermeability (thus enabling it to function as an LDH separator exhibiting hydroxide ion conductivity). The hydroxide ion-conducting layered compound 12b is particularly preferably embedded throughout the entire thickness direction of the polymer porous substrate 12a. The thickness of the LDH separator is preferably 3–80 μm, more preferably 3–60 μm, and even more preferably 3–40 μm.
[0117] The porous substrate 12a is made of a polymer material. The polymer porous substrate 12a has the following advantages: 1) it is flexible (therefore, even when thinned, it is not prone to cracking); 2) it easily increases porosity; 3) it easily increases conductivity (because although porosity is increased, the thickness can be reduced); 4) it is easy to manufacture and handle. Furthermore, it has the following advantages: 5) by fully utilizing the flexibility of 1) above, the LDH separator containing the porous substrate made of polymer material can be easily bent or sealed. Preferred examples of polymer materials include polystyrene, polyethersulfone, polypropylene, epoxy resin, polyphenylene sulfide, fluoropolymers (tetrafluoroethylene resin: PTFE, etc.), cellulose, nylon, polyethylene, and any combination thereof. From the viewpoint of thermoplastic resins suitable for heat pressing, more preferred examples include: polystyrene, polyethersulfone, polypropylene, epoxy resin, polyphenylene sulfide, fluoropolymers (tetrafluoroethylene resin: PTFE, etc.), nylon, polyethylene, and any combination thereof. All of the aforementioned preferred materials exhibit resistance to battery electrolytes, i.e., alkali resistance. Considering excellent resistance to hot water, acids, and alkalis, as well as low cost, polypropylene, polyethylene, and other polyolefins are particularly preferred polymeric materials, with polypropylene or polyethylene being the most preferred. When the porous substrate is composed of a polymeric material, it is particularly preferable that a hydroxide ion-conducting layered compound is embedded throughout the entire thickness direction of the porous substrate (for example, most or almost all of the pores inside the porous substrate are filled with the hydroxide ion-conducting layered compound). As such a polymeric porous substrate, a commercially available polymeric microporous membrane is preferably used.
[0118] The LDH separator of this scheme can be manufactured as follows: (i) using a polymer porous substrate, a composite material containing a hydroxide ion-conducting layered compound is produced according to a known method (see, for example, Patent Documents 1-3); (ii) the composite material containing the hydroxide ion-conducting layered compound is pressed. The pressing method can be, for example, roll pressing, uniaxial pressing, CIP (cold isostatic pressing), etc., without particular limitation, but roll pressing is preferred. By softening the polymer porous substrate, the pores of the porous substrate can be sufficiently sealed with the hydroxide ion-conducting layered compound; in this regard, it is preferable to perform the pressing while heating. As the temperature for sufficient softening, for example, in the case of polypropylene or polyethylene, heating is preferably performed at 60-200°C. By performing pressing such as roll pressing within such a temperature range, the average porosity caused by residual pores in the LDH separator can be significantly reduced. As a result, the LDH separator can be made extremely dense, thus further effectively suppressing short circuits caused by zinc dendrites. During roll forming, the morphology of residual pores can be controlled by appropriately adjusting the roll gap and roll temperature, thereby obtaining LDH partitions with the desired density or average porosity.
[0119] There is no particular limitation on the manufacturing method of the composite material containing hydroxide ion-conducting layered compound (i.e., coarse LDH separator) before pressing. It can be manufactured by appropriately modifying the conditions of known manufacturing methods of functional layers and composite materials containing LDH (i.e., LDH separators) (see, for example, Patent Documents 1-3). For example, the functional layer and composite material containing hydroxide ion-conducting layered compound (i.e., LDH separator) can be manufactured as follows: (1) Prepare a porous substrate; (2) Apply titanium oxide sol or a mixture of alumina and titanium dioxide sol to the porous substrate and perform heat treatment to form a titanium oxide layer or an alumina-titanium dioxide layer; (3) Impregnate the porous substrate with a solution containing nickel ions (Ni 2+ (3) In the raw material aqueous solution of urea; (4) The porous substrate is subjected to hydrothermal treatment in the raw material aqueous solution to form a functional layer containing hydroxide ion-conducting layered compound on and / or in the porous substrate. In particular, in the above step (2), by forming a titanium oxide layer or an alumina-titanium dioxide layer in the porous substrate, not only can the raw material of hydroxide ion-conducting layered compound be provided, but it can also be used as the starting point for the crystal growth of hydroxide ion-conducting layered compound, so that a highly dense functional layer containing hydroxide ion-conducting layered compound is uniformly formed in the porous substrate. In addition, urea is present in the above step (3), and ammonia is generated in the solution by the hydrolysis of urea, so that the pH value rises and the coexisting metal ions form hydroxide, thereby obtaining hydroxide ion-conducting layered compound. In addition, the hydrolysis is accompanied by the generation of carbon dioxide, so a hydroxide ion-conducting layered compound with carbonate ion as anion can be obtained.
[0120] In particular, when fabricating a composite material (i.e., an LDH separator) in which the porous substrate is made of a polymer material and the functional layer is embedded throughout the entire thickness direction of the porous substrate, it is preferable to apply the mixed sol of alumina and titanium dioxide to the substrate as described in (2) by a method that allows the mixed sol to penetrate into the entire or most of the interior of the substrate. Accordingly, most or almost all of the pores inside the porous substrate can be filled with a hydroxide ion-conducting layered compound. Examples of preferred coating methods include dip coating, filter coating, etc., with dip coating being particularly preferred. The amount of mixed sol adhered can be adjusted by adjusting the number of coatings in dip coating, etc. After the substrate coated with the mixed sol by dip coating, etc., is dried, the steps (3) and (4) described above can be performed.
[0121] LDH-like compounds
[0122] According to a preferred embodiment of the present invention, the LDH separator can be a separator containing an LDH-like compound. The definition of an LDH-like compound is as described above. Preferred LDH-like compounds are (a), (b), or (c) below.
[0123] (a) A layered crystalline hydroxide and / or oxide containing Mg and at least one element selected from the group consisting of Ti, Y and Al, that contains at least Ti.
[0124] (b) comprising (i) Ti, Y, and Al and / or Mg as desired, and (ii) at least one layered crystalline hydroxide and / or oxide selected from the group consisting of In, Bi, Ca, Sr and Ba, i.e., an added element M.
[0125] (c) Hydroxides and / or oxides containing Mg, Ti, Y, and, as desired, Al and / or In, with a layered crystalline structure.
[0126] In (c), the LDH-like compound exists in the form of a mixture with In(OH)3.
[0127] According to a preferred embodiment (a) of the invention, the LDH-like compound can be a layered crystalline hydroxide and / or oxide containing Mg and at least one element selected from the group consisting of Ti, Y, and Al. Therefore, a typical LDH-like compound is a complex hydroxide and / or complex oxide of Mg, Ti, Y (if desired), and Al (if desired). The aforementioned elements can be replaced by other elements or ions to the extent that they do not impair the fundamental properties of the LDH-like compound; however, the LDH-like compound preferably does not contain Ni. For example, the LDH-like compound may further contain Zn and / or K. Accordingly, the ionic conductivity of the LDH separator can be further improved.
[0128] LDH-like compounds can be identified using X-ray diffraction. Specifically, when X-ray diffraction is performed on the surface of an LDH separator, peaks originating from LDH-like compounds are typically detected in the range of 5° ≤ 2θ ≤ 10°, and more typically in the range of 7° ≤ 2θ ≤ 10°. As mentioned above, LDH is a substance having an alternating layered structure with exchangeable anions and H2O as intermediate layers between stacked hydroxide base layers. In this regard, when LDH is determined by X-ray diffraction, peaks originating from the crystalline structure of LDH (i.e., the (003) peak of LDH) are typically detected at a position of 2θ = 11 to 12°. In contrast, when LDH-like compounds are determined by X-ray diffraction, peaks are typically detected in the range of the aforementioned range, which is shifted to a lower angle than the aforementioned peak position of LDH. Furthermore, using 2θ corresponding to the peaks originating from LDH-like compounds in X-ray diffraction, the interlayer distance of the layered crystalline structure can be determined according to the Bragg formula. The interlayer distances of the layered crystal structures that constitute LDH-like compounds are typically 0.883–1.8 nm, and more typically 0.883–1.3 nm.
[0129] Regarding the LDH separator of the above scheme (a), the atomic ratio of Mg / (Mg+Ti+Y+Al) in the LDH-like compound, determined by energy dispersive X-ray analysis (EDS), is preferably 0.03 to 0.25, more preferably 0.05 to 0.2. Furthermore, the atomic ratio of Ti / (Mg+Ti+Y+Al) in the LDH-like compound is preferably 0.40 to 0.97, more preferably 0.47 to 0.94. Additionally, the atomic ratio of Y / (Mg+Ti+Y+Al) in the LDH-like compound is preferably 0 to 0.45, more preferably 0 to 0.37. Moreover, the atomic ratio of Al / (Mg+Ti+Y+Al) in the LDH-like compound is preferably 0 to 0.05, more preferably 0 to 0.03. Within these ranges, the alkali resistance is superior, and the effect of suppressing short circuits caused by zinc dendrites (i.e., dendrite tolerance) can be achieved more effectively. However, regarding the LDH separator, the basic composition of LDH, as previously known, can be expressed by the general formula: M 2+ 1-x M 3+ x (OH)2A n- x / n ·mH2O (where M) 2+ M is a divalent cation. 3+ A is a trivalent cation. n-The term "anion with an n-valence, where n is an integer greater than or equal to 1, x is 0.1 to 0.4, and m is 0 or greater" is used. In contrast, the atomic ratios in LDH-like compounds generally deviate from the general formula for LDH. Therefore, it can be said that the LDH-like compounds in this scheme generally have different compositional ratios (atomic ratios) than conventional LDH. It should be noted that EDS analysis is preferably performed as follows: using an EDS analysis apparatus (e.g., X-act, manufactured by Oxford Instruments), 1) images are acquired at an accelerating voltage of 20 kV and a magnification of 5,000x; 2) in point analysis mode, with intervals of approximately 5 μm, three-point analysis is performed; 3) steps 1) and 2) are repeated once more; 4) the average value of the six points is calculated.
[0130] According to another preferred embodiment (b) of the invention, the LDH-like compound can be a layered crystalline hydroxide and / or oxide comprising (i) Ti, Y, and, depending on the desired inclusion of Al and / or Mg, and (ii) an additive element M. Thus, a typical LDH-like compound is a complex hydroxide and / or complex oxide comprising Ti, Y, an additive element M, and, depending on the desired inclusion of Al and Mg. The additive element M is In, Bi, Ca, Sr, Ba, or a combination thereof. The aforementioned elements can be substituted by other elements or ions to the extent that they do not impair the fundamental properties of the LDH-like compound; however, the LDH-like compound preferably does not contain Ni.
[0131] Regarding the LDH separator of scheme (b) above, the atomic ratio of Ti / (Mg+Al+Ti+Y+M) in the LDH-like compound, as determined by energy dispersive X-ray diffraction (EDS), is preferably 0.50 to 0.85, more preferably 0.56 to 0.81. The atomic ratio of Y / (Mg+Al+Ti+Y+M) in the LDH-like compound is preferably 0.03 to 0.20, more preferably 0.07 to 0.15. The atomic ratio of M / (Mg+Al+Ti+Y+M) in the LDH-like compound is preferably 0.03 to 0.35, more preferably 0.03 to 0.32. The atomic ratio of Mg / (Mg+Al+Ti+Y+M) in the LDH-like compound is preferably 0 to 0.10, more preferably 0 to 0.02. Furthermore, the atomic ratio of Al / (Mg+Al+Ti+Y+M) in the LDH-like compound is preferably 0 to 0.05, more preferably 0 to 0.04. Within the aforementioned range, the alkali resistance is even better, and it can more effectively suppress short circuits caused by zinc dendrites (i.e., dendrite tolerance). However, regarding LDH separators, the previously known basic composition of LDH can be expressed by the general formula: M 2+ 1-x M 3+ x (OH)2A n-x / n ·mH2O (where M) 2+ M is a divalent cation. 3+ A is a trivalent cation. n- The term "anion with an n-valence, where n is an integer greater than or equal to 1, x is 0.1 to 0.4, and m is 0 or greater" is used. In contrast, the atomic ratios in LDH-like compounds generally deviate from the general formula for LDH. Therefore, it can be said that the LDH-like compounds in this scheme generally have different compositional ratios (atomic ratios) than conventional LDH. It should be noted that EDS analysis is preferably performed as follows: using an EDS analysis apparatus (e.g., X-act, manufactured by Oxford Instruments), 1) images are acquired at an accelerating voltage of 20 kV and a magnification of 5,000x; 2) in point analysis mode, with intervals of approximately 5 μm, three-point analysis is performed; 3) steps 1) and 2) are repeated once more; 4) the average value of the six points is calculated.
[0132] According to another preferred embodiment (c) of the invention, the LDH-like compound can be a layered crystalline hydroxide and / or oxide containing Mg, Ti, Y, and, as desired, Al and / or In, and the LDH-like compound exists in the form of a mixture with In(OH)3. The LDH-like compound of this embodiment is a layered crystalline hydroxide and / or oxide containing Mg, Ti, Y, and, as desired, Al and / or In. Therefore, a typical LDH-like compound is a complex hydroxide and / or complex oxide of Mg, Ti, Y, and, as desired, Al, and, as desired, In. It should be noted that the In that may be contained in the LDH-like compound can be intentionally added to the LDH-like compound or unavoidably mixed into the LDH-like compound due to the formation of In(OH)3, etc. The above-mentioned elements can be replaced by other elements or ions to the extent that they do not impair the basic properties of the LDH-like compound; however, the LDH-like compound preferably does not contain Ni. However, regarding the LDH separator, the basic composition of the previously known LDH can be expressed by the general formula: M 2+ 1-x M 3+ x (OH)2A n- x / n ·mH2O (where M) 2+ M is a divalent cation. 3+ A is a trivalent cation. n- (where n is an n-valent anion, n is an integer greater than or equal to 1, x is 0.1 to 0.4, and m is 0 or greater). In contrast, the atomic ratios in LDH-like compounds generally deviate from the above general formula for LDH. Therefore, it can be said that the LDH-like compounds in this scheme generally have different compositional ratios (atomic ratios) than conventional LDHs.
[0133] The mixture in scheme (c) above contains not only an LDH-like compound but also In(OH)3 (typically composed of an LDH-like compound and In(OH)3). The presence of In(OH)3 effectively improves the alkali resistance and dendrite resistance of the LDH separator. The preferred proportion of In(OH)3 in the mixture is one that improves alkali resistance and dendrite resistance with minimal impairment to the hydroxide ion conductivity of the LDH separator, but there is no particular limitation. In(OH)3 can have a cubic crystalline structure or be composed of In(OH)3 crystals surrounded by an LDH-like compound. In(OH)3 can be identified using X-ray diffraction.
Claims
1. An air electrode / separator joint, wherein, have: A hydroxide ion-conducting separator containing a hydroxide ion-conducting solid electrolyte; An air electrode layer with a thickness of less than 1000 nm is disposed on one side of the hydroxide ion-conducting separator and comprises a hydroxide ion-conducting material, an electron-conducting material, and an air electrode catalyst. The hydroxide ion-conducting material is the same material as the hydroxide ion-conducting solid electrolyte or the air electrode catalyst. Furthermore, the electron-conducting material is the same material as the air electrode catalyst. The air electrode / separator junction also includes an interface layer between the hydroxide ion-conducting separator and the air electrode layer. The interface layer includes: Multiple plate-shaped particles are composed of a hydroxide ion-conducting solid electrolyte that grows in a direction away from the surface of the hydroxide ion-conducting separator; An electronically conductive material configured to fill the gaps between the plurality of plate-like particles and / or the irregularities formed by the plurality of plate-like particles.
2. The air electrode / separator joint according to claim 1, wherein, The air electrode layer comprises: Multiple electronically conductive units are disposed on the interface layer with gaps between them and are made of the electronically conductive material; and The hydroxide ion-conducting material and the air electrode catalyst are disposed on the electron conduction unit.
3. The air electrode / separator joint according to claim 1 or 2, wherein, The thickness of the interface layer is less than 150 nm, and the thickness of the air electrode layer is less than 300 nm.
4. The air electrode / separator joint according to claim 1 or 2, wherein, The hydroxide ion-conducting material contained in the air electrode layer is a layered double hydroxide (LDH) and / or an LDH-like compound. The electron-conducting material contained in the air electrode layer is at least one selected from the group consisting of metallic materials, conductive ceramics, and carbon materials. The air electrode catalyst contained in the air electrode layer is selected from at least one of the following groups: layered double hydroxide (LDH) and other metal hydroxides, metal oxides, metal nanoparticles and carbon materials.
5. The air electrode / separator joint according to claim 1 or 2, wherein, The hydroxide ion-conducting solid electrolyte contained in the interface layer is a layered double hydroxide (LDH) and / or an LDH-like compound.
6. The air electrode / separator joint according to claim 1 or 2, wherein, The hydroxide ion-conducting solid electrolyte is a layered double hydroxide (LDH) and / or an LDH-like compound, thereby the hydroxide ion-conducting separator becomes an LDH separator.
7. The air electrode / separator joint according to claim 6, wherein, The LDH partition is composited with a porous substrate.
8. A metal-air secondary battery, wherein, It comprises: an air electrode / separator assembly as described in claim 1 or 2, a metal negative electrode, and an electrolyte, wherein the electrolyte is separated from the air electrode layer by means of the hydroxide ion-conducting separator.
Citation Information
Patent Citations
Zinc-air secondary battery
WO2013073292A1
Air electrode for metal-air battery
WO2015146671A1
Method for forming layered double hydroxide dense membrane
WO2016067884A1
Separator structure body for use in zinc secondary battery
WO2016076047A1
Air electrode / separator assembly and metal-air secondary battery
WO2020246176A1